1997
DOI: 10.1063/1.119850
|View full text |Cite
|
Sign up to set email alerts
|

Lithium–aluminum contacts for organic light-emitting devices

Abstract: Organic light-emitting devices have been prepared with multilayer Al–Li–Al cathodes in an ultrahigh vacuum molecular beam deposition system. The optimum device characteristics are obtained when there is a single Al layer separating the Li layer from the organic materials. Ab initio molecular dynamics calculations of the Al–Li interaction clarify the role of Al as a blocking layer to Li diffusion into the organic films as well as the behavior of the device when the thickness of this Al interfacial layer is chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 13 publications
0
67
0
Order By: Relevance
“…OLEDs with an alloy interface between the cathode and the polymer have been found to be superior, in terms of lifetime and luminosity, to those with singleelement cathodes. 3,4 Thus the relationship between Φ and stability 5 is crucial. However, it is poorly understood, especially for more complex metals.…”
Section: Introductionmentioning
confidence: 99%
“…OLEDs with an alloy interface between the cathode and the polymer have been found to be superior, in terms of lifetime and luminosity, to those with singleelement cathodes. 3,4 Thus the relationship between Φ and stability 5 is crucial. However, it is poorly understood, especially for more complex metals.…”
Section: Introductionmentioning
confidence: 99%
“…61 Intrinsic deteriorations involve problems in the stability of organic thin fi lm, interface between anode and organic layer, excited state stability, movement of ionic impurity, diffusion of transparent electrode metal into emission layer (indium migration mechanism), cation instability, large energy barrier for charge carriers, positive charges accumulation, and width of recombination zone. 56,57,61,63,69,70,[72][73][74][75][76][77] Adachi's group has reported that a large energy barrier for hole injection at the interface of ITO/HTL (hole transporting layer) would lead to large joule heat generation. The produced heat would steadily cause local aggregation of organic molecules such as dimerization and crystallization of an amorphous HTL.…”
Section: Failure Mechanismsmentioning
confidence: 99%
“…73 Diffusion of electrode metal ions into the device's organic layers and its effect on device performance have been extensively studied in the last two decades. 62,[75][76][77][78][79] Electrode metal ions were moved due to an electric fi eld constructed by direct current and reduced the device lifetime. 75 Haskal et al 76 reported that the lithium (Li) diffused rapidly into organic materials from a Li/Al cathode, and thus shortened the device lifetime.…”
Section: Failure Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Hasakl et al showed that a buffer layer of Al between lithium and tris͑8-hydroxyquinolino͒aluminum (Alq 3 ) enhances the performance of pLEDs. 4 Note, that after the deposition of an organic material on a metal layer a diffusive layer has also been observed. Huang et al reported that a thin aluminum oxide layer helps to hinder the diffusion of Al into the deposited Alq 3 layer.…”
Section: Introductionmentioning
confidence: 99%